The Role of Village Facilitators in Optimizing Rural Development in Gattareng Village, Pujananting District, Barru Regency - Sri Hardianti Lukman; Rahmi Rais (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal